2022
DOI: 10.1039/d2cp02381d
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 2D/2D BiOBr/g-C3N4 with efficient photocatalytic activity and clarification of its mechanism

Abstract: Precise regulating photoexcited charge carrier for separation-transportation is a core for practical application in the photocatalysis field. Herein, 2D/2D BiOBr/g-C3N4 heterojunction is prepared by a self-assembly method and exhibits enhanced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…[ 38 ] Under light illumination, ZIS/In 2 O 3 hybrid exhibited a higher photocurrent density ( Figure a) and a smaller charge transfer resistance (Figure 6b) than those of bare ZIS and In 2 O 3 , indicating that the ZIS/In 2 O 3 possessed much‐enhanced charge separation efficiency and transfer ability. [ 49 ] For photocatalysts, the shorter emission lifetime represents that the photogenerated charge carriers can be better separated, [ 52,53 ] and as expected, Figure 6c showed that the average emission lifetime of ZIS/In 2 O 3 (3.71 ns) was shorter than that of ZIS (6.72 ns) and In 2 O 3 (9.23 ns). These characterizations well certified that the construction of ZIS/In 2 O 3 heterostructure endowed this composite with a highly ameliorated charge separation and transport, therefore achieving the optimum catalytic activity.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…[ 38 ] Under light illumination, ZIS/In 2 O 3 hybrid exhibited a higher photocurrent density ( Figure a) and a smaller charge transfer resistance (Figure 6b) than those of bare ZIS and In 2 O 3 , indicating that the ZIS/In 2 O 3 possessed much‐enhanced charge separation efficiency and transfer ability. [ 49 ] For photocatalysts, the shorter emission lifetime represents that the photogenerated charge carriers can be better separated, [ 52,53 ] and as expected, Figure 6c showed that the average emission lifetime of ZIS/In 2 O 3 (3.71 ns) was shorter than that of ZIS (6.72 ns) and In 2 O 3 (9.23 ns). These characterizations well certified that the construction of ZIS/In 2 O 3 heterostructure endowed this composite with a highly ameliorated charge separation and transport, therefore achieving the optimum catalytic activity.…”
Section: Resultssupporting
confidence: 60%
“…Generally, the negative and positive shifts of the XPS peaks tend to represent the increase and decrease of electron density, respectively. [ 30,31,52 ] Therefore, the binding energy shifts manifested that the charge carriers (electrons for n‐type semiconductors) migrated from In 2 O 3 into ZIS. When the equilibrium is achieved, the IEF can be built at the interfaces of ZIS/In 2 O 3 heterostructure with a direction of In 2 O 3 → ZIS.…”
Section: Resultsmentioning
confidence: 99%